In vitro anthelmintic activity of Physalis minima ethanolic leaves and stem extracts against Paramphistomum cervi from cattle - Ahmed, Fazle Rabbi Shakil (2023)
Crude ethanolic extracts of leaves and stem of Physalis minima (Solanaceae) were evaluated for in vitro anthelmintic activity on the Bangladeshi mature parasitic flatworm Paramphistomum cervi (Trematoda) in cattle. To compare the test results, Albendazole was used as a standard drug.